New Podoscirtine crickets (Orthoptera: Gryllidae; Podoscirtinae) from National Natural Park Amacayacu, Amazonas, Colombia - Cadena-Castañeda, Oscar J.; Noriega, Jorge Ari (Zootaxa, 2015)
We describe six new species of crickets from the subfamily Podoscirtinae in the family Gryllidae from the “Amacayacu” National Park: Diatrypa (Latispeculum) didieri n. sp. (Aphonoidini: Diatrypina), Ectotrypa brachyptera n. sp. (Paroecanthini: Paroecanthina), Aphonomorphus (Aphonomorphus) desutterae n. sp., Aphonomorphus (Euaphonus) andreae n. sp., Aphonomorphus (Euaphonus) gorochovi n. sp., and Aphonomorphus (Nigraphonus) otavoi n. sp. (Podoscirtini: Aphonomorphina). Nigraphonus n. subgen. is proposed as a new subgenus of Aphonomorphus, grouping the species with unclear position into Neoaphonus (A. obscurus Chopard, 1956 n. comb., A. parobscurus Gorochov, 2010 n. comb., and A. nigra n. sp.). The state of knowledge of Podoscirtinae in Colombia is discussed.